Proposals to amalgamate the National and University Libraries in Reykjavik and to build a new national and university library: Iceland - (mission) 23-29 October 1969 - Carter, Edward J.; Tveterås, Harald L. (Paris, December 1969, 1969)
Mission report on a proposed library building to combine the present national library and university libraries in Iceland